0
$\begingroup$

$$ \begin{cases} \sigma_{1,(2)}=x_1+x_2\\ \sigma_{2,(2)}=x_1x_2\\ \end{cases}\\ \color{red}{ \begin{align*} &&p_2&=\sqrt{x_1}+\sqrt{x_2}\\ &\Rightarrow&\left({p_2}^2-\sigma_{1,(2)}\right)^2&=4\sigma_{2,(3)}\\ \end{align*}} $$ $$ \begin{cases} \sigma_{1,(3)}=x_1+x_2+x_3\\ \sigma_{2,(3)}=x_1x_2+x_1x_3+x_2x_3\\ \sigma_{3,(3)}=x_1x_2x_3 \end{cases}\\ \color{red}{ \begin{align*} &&p_3&=\sqrt{x_1}+\sqrt{x_2}+\sqrt{x_3}\\ &\Rightarrow&\left[\left({p_3}^2-\sigma_{1,(3)}\right)^2-4\sigma_{2,(3)}\right]^2&=64{p_3}^2\sigma_{3,(3)}\\ \end{align*}} $$ What about the situation of more variables?

How to rationalize it $$p_4=\sqrt{x_1}+\sqrt{x_2}+\sqrt{x_3}+\sqrt{x_4}$$

I have ran it above through Wolfram Mathematica and no result return.

$\endgroup$
  • $\begingroup$ What exactly do you mean by "rationalising" the expression? $\endgroup$ – Theo Bendit Feb 26 at 9:51
  • $\begingroup$ @TheoBendit Conversion to polynomial equation with symmetric polynomial $\endgroup$ – D.Matthew Feb 26 at 9:56
0
$\begingroup$

\begin{gather*} &\left(\left(\left(p^2-\sigma_{1,(4)}\right)^2-4\sigma_{2,(4)}\right)^2-64p^2\sigma_{3,(4)}+64\sigma_{4,(4)}\right)^2\\ {\large=}&256\sigma_{4,(4)}\left(3p^4-2p^2\sigma_{1,(4)}-{\sigma_{1,(4)}}^2+4\sigma_{2,(4)}\right)^2 \end{gather*} \begin{cases} \sigma_{1,(4)}=x_1+x_2+x_3+x_4\\ \sigma_{2,(4)}=x_1x_2+x_1x_3+x_1x_4+x_2x_3+x_2x_4+x_3x_4\\ \sigma_{3,(4)}=x_1x_2x_3+x_2x_3x_4+x_1x_3x_4+x_1x_2x_4\\ \sigma_{4,(4)}=x_1x_2x_3x_4\\ \end{cases} \begin{gather*} p=\sqrt{x_1}+\sqrt{x_2}+\sqrt{x_3}+\sqrt{x_4} \end{gather*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.